Florida Crop/Pest Management Profile: Lettuce - Mark A. Mossler; Esther Dunn (EDIS)
This document is CIR1460, one of a series of the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2005.